Dental Approach to the Hypertensive Patient: Literature Review - Ferreira Do Amaral, Cristhiane Olivia; Nascimento Neves, Angela Maria; Santos, Thais De Almeida; Ferreira Do Amaral, Mariana Olivia; Straioto, Fabiana Gouveia (European Scientific Journal, ESJ, 2022)
Hypertensive patients deserve special attention, due to possible complications which may occur during invasive dental care. This manuscript aimed at reviewing the literature as follows: a safe dental approach to hypertensive patients, local anesthetics indication, surgical risks, hypertensive crisis, drug interactions, and oral manifestations of antihypertensive drug use. The present study was developed by research in the following databases: Virtual Health Library (VHL) – Bireme, MEDLINE, PubMed, SciELO, and the Capes database Journals. For a safe approach to the hypertensive patient, some precautions must be taken and respected such as adequate anamnesis is essential to evaluate other associated systemic alterations (cardiovascular, diabetes, renal failure), measure blood pressure at the beginning of the procedure, and, in case of longer procedures, monitor blood pressure during the intervention, minimize chair time for the sake of the patient anxiety. Medication regarding stress reduction control can be used to prevent high blood pressure from emotional conditions as well as choosing the appropriate anesthetic. Solutions with vasoconstrictor lower concentration, respecting the dose, and following the principles of the anesthetic technique must be observed. Non-steroidal anti-inflammatory drug use should be avoided. These precautions will avoid serious iatrogenic events in addition to promoting and guaranteeing the patient safe and quality care.